Modifikasi Sudu-sudu Blower Sentrifugal yang Diaplikasikan pada Turbin Pico Hydro - Z, Zulfikar; D, Dean Corio (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
The water turbine must be specially designed according to the calculation of its energy potential, proportional to the height of the falling water and the discharge. This research is conducted to study the solution fluid engine that functions as a pico hydro water turbine, namely a centrifugal blower with a simple construction, operating at low head, small discharge, easy installation and operation and low price. The blower used in this test is a blower that is already on the market with an impeller diameter of 15 cm, inlet size of 2 inches. The test was carried out at a constant head (falling water height) of 5 m. The working principle of the blower is reversed, that is, water from a certain height flows through the rapid pipe and enters the exhaust side of the blower until the water moves the blower and exits through the blower inlet to the draftube. The purpose of this study was to determine the effect of modification of the blades on the increase in efficiency of the picohydro turbine. This study uses an analytical method with testing parameters based on calculating the value of water discharge, water power, torque, turbine mechanical power and turbine efficiency. To increase the power and efficiency of the blower as a turbine, modifications are made to the blower blades. With the modification of the blower blades, the turbine efficiency increases by 10 percents from before the modification.